Analisis Minat Belajar Mahasiswa dalam Pembelajaran E-Learning Google Classroom pada Mahasiswa S2 Teknologi Pendidikan - Susanto, Joko; Tiur Maria S, Haratua; Karolina, Venny (Peneliti.net, 2024)
In the current digital era, education is increasingly shifting towards the use of online technology. E-Learning, as a form of distance education, has become a significant phenomenon in the learning process. This research aims to analyze the learning interest of Master of Educational Technology students at Tanjungpura University in using Google Classroom E-Learning. Quantitative methods with a descriptive approach were used in this research, by collecting data through online questionnaires to 27 students. The results of the analysis show that even though the data is not normally distributed, there is significant interest in learning towards Google Classroom E-Learning with an average score of 3.1254 on a Likert scale range of 1 to 4. Developing teaching methods, further research regarding factors that influence interest in learning, more intensive technical support, and regular evaluation and feedback are some of the suggestions suggested to improve the quality of online learning. Understanding more deeply about students' learning interest in Google Classroom E-Learning will help develop a more adaptive approach according to students' needs in the future. Keywords: E-learning, Interest in learning, Google Classroom